2014
DOI: 10.3409/fb62_4.345
|View full text |Cite
|
Sign up to set email alerts
|

<I>In Vitro</I> Ruminal Fluid Fermentation as Influenced by Corn-Derived Dried Distillers' Grains with Solubles

Abstract: In vitro ruminal fluid fermentation as influenced by corn-derived dried distillers' grains with solubles. Folia Biologica (Kraków) 62: 345-351. This study was conducted to evaluate changes to in vitro ruminal fluid fermentation due to the use of corn-derived dried distillers' grains with solubles (corn DDGS) as a partial or complete replacement for crushed cereal and oilseed meals in the fermentation substrate. The control substrate consisted of mixed cereal and oilseed meals (barley, wheat, soybean and rapese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 19 publications
6
12
0
Order By: Relevance
“…In our study, a slight decrease in methanogenesis was found in group D3 in the 24-hour fermentation period, where the lowest pH was observed. The effect of the fermentation time on pH value in the analysed samples was noticed, and it corresponds to earlier research (Miśta et al 2014). …”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…In our study, a slight decrease in methanogenesis was found in group D3 in the 24-hour fermentation period, where the lowest pH was observed. The effect of the fermentation time on pH value in the analysed samples was noticed, and it corresponds to earlier research (Miśta et al 2014). …”
Section: Discussionmentioning
confidence: 68%
“…However, the effect of DDGS on the increase in total gas production was observed in this study. Conversely, earlier in vitro research in cows showed a decrease in both methanogenesis and total gas production (Miśta et al 2014). The greatest drop in gas production was observed in the samples containing 100% DDGS in In vitro study of the effect of corn dried distillers grains...…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations